Approaches to Active Labour Market Policy in The Slovak Republic, Czech Republic and in Finland - Lubica Konusikova; Alzbeta Kucharcikova (Komunikácie : vedecké listy Žilinskej univerzity = Communications : scientific letters of the University of Žilina, 2015)
The subject matter of the article consists in the issue of unemployment, which is the problem in many countries. The article describes approaches to the solution of the unemployment from the point of view of several economic specializations in theory. Active labour-market policies have developed significantly over the past two decades across Organization for Economic Cooperation and Development (OECD). This article describes the approaches to the solution of unemployment problem of the Czech Republic, Slovak Republic and Finland. Objective of this article is to account variant of active labour market policy.